The Effects of Chromium and Vanadium on Biomarkers of Carbohydrate and Lipid Metabolism in Workers Exposed to Coal Fly Ash - Lulzim Zeneli; Majlinda Daci-Ajvazi; Ankica Sekovanić; Jasna Jurasović; Demush Bajraktari (MDPI AG, 2022)
Chromium (Cr) and vanadium (V) are micronutrients playing a role in carbohydrate and lipid metabolism but can be toxic at high concentrations, especially in specific forms. The study documents the effect of Cr and V concentrations on glucose and lipid metabolism in workers exposed to coal fly ash. We quantified selected metals (Cr, V) in the blood and serum of workers from a thermal power plant in Kosovo and compared them with the reference biological values. We determined fasting serum glucose and lipid profiles using a biochemical analyzer Synchron CX7 (Beckman Coulter). We quantified blood and serum Cr and V by inductively coupled plasma mass spectrometry. We also evaluated the association between carbohydrate and lipid metabolism biomarkers (glucose, cholesterol, and triglycerides) and co-exposure to coal fly ash. Power plant workers had significantly higher blood Cr and V levels (p < 0.0001) and significantly lower serum Cr and V levels (p < 0.0001) than the controls. We also found statistically significant (p < 0.0001) correlations between high blood Cr levels and low glucose/blood Cr ratios as well as between high serum Cr levels and low glucose/serum Cr ratios. Finally, in power plant workers, high blood V levels significantly correlated with low triglycerides/blood V and cholesterol/blood V ratios (p < 0.0001), while high serum V levels correlated with low cholesterol/serum V ratios (p = 0.005). Based on these findings, we concluded that the glucose/Cr, triglycerides/V and cholesterol/V ratios should be considered when evaluating carbohydrate and lipid metabolism disorders in occupationally-exposed workers.